2010
DOI: 10.1002/biof.103
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite—An ugly biofactor?

Abstract: Cellular damage occurring under oxidative conditions has been ascribed mainly to the formation of peroxynitrite (ONOOH/ONOO(-)) that originates from the reaction of NO(*) with O(2) (*-). The detrimental effects of peroxynitrite are exacerbated by the reaction with CO(2) that leads to ONOOC(O)O(-), which further decays to the strong oxidant radicals NO(2) (*) and CO(3) (*-). The reaction with CO(2), however, may redirect peroxynitrite specificity. An excessive formation of peroxynitrite represents an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 161 publications
1
44
0
1
Order By: Relevance
“…We previously showed that TNF-α directly impairs pulmonary artery endothelialdependent relaxation mediated by stimulation of ROS generation and NO synthase uncoupling (El-Bassossy et al 2009). The role of reactive nitrogen species (nitrosative stress) and associated pathways in the pathogenesis of cardiovascular disease has been widely accepted (Ascenzi et al 2010). TNF-α can also impair vascular contractility indirectly through stimulation of leukocytes infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that TNF-α directly impairs pulmonary artery endothelialdependent relaxation mediated by stimulation of ROS generation and NO synthase uncoupling (El-Bassossy et al 2009). The role of reactive nitrogen species (nitrosative stress) and associated pathways in the pathogenesis of cardiovascular disease has been widely accepted (Ascenzi et al 2010). TNF-α can also impair vascular contractility indirectly through stimulation of leukocytes infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, besides this, ONOO -exhibits significant biomedical effects -protective effect i) at high concentrations -it behaves as anti-viral, anti-microbial, and anti-parasitic agent, and ii) at low concentrations, it stimulates protective mechanisms in the cardiovascular, nervous, and respiratory systems (Ascenzi et al 2010).…”
Section: Biomedical and Therapeutical Importancementioning
confidence: 99%
“…ONOO − and its derivatives (e.g. nitrogen dioxide (·NO 2 ), dinitrogen trioxide (N 2 O 3 ) and peroxynitrous acid (ONOOH)) can easily penetrate the cellular membrane and modify proteins, lipids and DNA [13,33]. In cells, ONOO − mediates nitration of tyrosine and tryptophan residues and Snitrosylation of thiol group in proteins, which in turn modifies their functions [79,181] (Fig.…”
Section: Nadph Oxidases In the Vascular Systemmentioning
confidence: 98%